Separate and warring selves : identity crises in Africa in Shiva Naipaul's "North of South: an African journey" - Coetsee, Jarryd (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English Studies))--University of Stellenbosch, 2009.